2014
DOI: 10.1111/bjh.13119
|View full text |Cite
|
Sign up to set email alerts
|

Defining serum ferritin thresholds to predict clinically relevant liver iron concentrations for guiding deferasirox therapy when MRI is unavailable in patients with non‐transfusion‐dependent thalassaemia

Abstract: SummaryLiver iron concentration (LIC) assessment by magnetic resonance imaging (MRI) remains the gold standard to diagnose iron overload and guide iron chelation therapy in patients with non‐transfusion‐dependent thalassaemia (NTDT). However, limited access to MRI technology and expertise worldwide makes it practical to also use serum ferritin assessments. The THALASSA (assessment of Exjade® in non‐transfusion‐dependent THALASSemiA patients) study assessed the efficacy and safety of deferasirox in iron‐overloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…In Group 1 subjects, 89% had LIC of ≥5 mg/g dw, of which 25% had corresponding serum ferritin of <500 μg/l (with the lowest serum ferritin being 224 μg/l). A serum ferritin of ≥800 μg/l proposed by Taher et al () had the lowest NPV among our patients with HbHCS for predicting LIC of ≥5 mg/g dw, and might cause delay in initiation of iron chelation in 67·7% (or 1‐NPV) of the patients if this serum ferritin threshold was adopted when MRI was unavailable. This risk of delay in iron chelation therapy was higher than the 43·9% in our deletional HbH disease patients and the 46·4% in NTDT patients reported in the study by Taher et al () (Table ).…”
Section: Ppv and Npv Using Serum Ferritin Of ≥800 μG/l For Initiationmentioning
confidence: 69%
See 1 more Smart Citation
“…In Group 1 subjects, 89% had LIC of ≥5 mg/g dw, of which 25% had corresponding serum ferritin of <500 μg/l (with the lowest serum ferritin being 224 μg/l). A serum ferritin of ≥800 μg/l proposed by Taher et al () had the lowest NPV among our patients with HbHCS for predicting LIC of ≥5 mg/g dw, and might cause delay in initiation of iron chelation in 67·7% (or 1‐NPV) of the patients if this serum ferritin threshold was adopted when MRI was unavailable. This risk of delay in iron chelation therapy was higher than the 43·9% in our deletional HbH disease patients and the 46·4% in NTDT patients reported in the study by Taher et al () (Table ).…”
Section: Ppv and Npv Using Serum Ferritin Of ≥800 μG/l For Initiationmentioning
confidence: 69%
“…However, due to the cost and limited availability of MRI, serum ferritin is often used as a surrogate marker of liver and body iron load in thalassaemia patients. Taher et al () recently reported good correlation between serum ferritin and LIC in a large NTDT population comprising HbE/β thalassaemia, β thalassaemia intermedia and HbH disease, and advocated a serum ferritin threshold of 800 μg/l for initiation of chelation therapy when MRI assessment of LIC was unavailable. This threshold had the highest overall accuracy in their cohort of patients for predicting LIC of ≥5 mg/g dry weight (dw), with positive and negative predictive values (NPV) of 91·7% and 53·6%, respectively (Taher et al , ).…”
Section: Ppv and Npv Using Serum Ferritin Of ≥800 μG/l For Initiationmentioning
confidence: 99%
“…We recommend that MRI LIC measurement should be performed in all patients. Recently, in a study in non‐transfusion dependent thalassemia patients, a ferritin cut‐off of 800 ng/mL was demonstrated to have the best predictive value for iron overload (defined as LIC ≥ 5 mg/g) when MRI is unavailable 2. Both in our rare HHA sample and in the reference group, the sensitivity of a cut‐off of 800 ng/mL for LIC ≥ 7 mg/g remained poor.…”
Section: Figurementioning
confidence: 76%
“…The LIC of ≥5 mg Fe/g dry weight indicates the status of iron overload requiring appropriate iron chelation [18]. In the THALASSA (Assessment of Exjade® in Non-Transfusion-Dependent Thalassemia Patients) study by Taher et al [19], a serum ferritin level of ≥800 ng/ml had the highest positive predictive value of 91.7% for LIC ≥5 mg Fe/g dry weight. However, the normal levels of serum ferritin are 12-300 ng/ml for males and 12-150 ng/ml for females.…”
Section: Discussionmentioning
confidence: 99%